Acute Kidney Injury Associates with Long-Term Increases in Plasma TNFR1, TNFR2, and KIM-1: Findings from the CRIC Study. Issue 6 (June 2022) - McCoy, Ian E.; Hsu, Jesse Y.; Bonventre, Joseph V.; Parikh, Chirag R.; Go, Alan S.; Liu, Kathleen D.; Ricardo, Ana C.; Srivastava, Anand; Cohen, Debbie L.; He, Jiang; Chen, Jing; Rao, Panduranga S.; et al.
Significance Statement: Levels of TNF receptors 1 and 2 (TNFR1 and TNFR2) and kidney injury molecule 1 (KIM-1) vary considerably among patients with CKD; those with higher levels have faster subsequent disease progression. The reasons why some individuals have higher levels of biomarkers of inflammation and injury are unknown. In this observational cohort study, the authors investigated whether these higher biomarker levels reflect effects of prior episodes of AKI. They found that levels of TNFR1, TNFR2, and KIM-1 in banked plasma samples increased after AKI, and these elevations persist for months, a longer timeframe than examined in prior studies. These findings may provide insight into the pathophysiology of kidney disease progression and the potential role of AKI episodes punctuating the course of CKD. Visual Abstract: Abstract : Background: Some markers of inflammation—TNF receptors 1 and 2 (TNFR1 and TNFR2)—are independently associated with progressive CKD, as is a marker of proximal tubule injury, kidney injury molecule 1 (KIM-1). However, whether an episode of hospitalized AKI may cause long-term changes in these biomarkers is unknown. Methods: Among adult participants in the Chronic Renal Insufficiency Cohort (CRIC) study, we identified 198 episodes of hospitalized AKI (defined as peak/nadir inpatient serum creatinine values ≥1.5). For each AKI hospitalization, we found the best matched non-AKI hospitalization (unique patients), using prehospitalization characteristics, including eGFR and urine protein/creatinine ratio. We measured TNFR1, TNFR2, and KIM-1 in banked plasma samples collected at annual CRIC study visits before and after the hospitalization (a median of 7 months before and 5 months after hospitalization). Results: In the AKI and non-AKI groups, we found similar prehospitalization median levels of TNFR1 (1373 pg/ml versus 1371 pg/ml, for AKI and non-AKI, respectively), TNFR2 (47, 141 pg/ml versus 46, 135 pg/ml, respectively), and KIM-1 (857 pg/ml versus 719 pg/ml, respectively). Compared with matched study participants who did not experience AKI, study participants who did experience AKI had greater increases in TNFR1 (23% versus 10%, P <0.01), TNFR2 (10% versus 3%, P <0.01), and KIM-1 (13% versus −2%, P <0.01). Conclusions: Among patients with CKD, AKI during hospitalization was associated with increases in plasma TNFR1, TNFR2, and KIM-1 several months after their hospitalization. These results highlight a potential mechanism by which AKI may contribute to more rapid loss of kidney function months to years after the acute insult.